Successful Conservative Management of Premature Rupture Membranes of Twin Pregnancy with one Fetus Papyraceus - Ketut Edy Sudiarta (Institute of Medico-legal Publications Pvt Ltd, 2021)
Fetus papyraceus is a rare obstetrics complication and is characterized by the death of one or more fetuses inthe early gestation period, and the other fetus continues to develop. This report describes a twin pregnancywith one fetus papyraceus and both undergone premature membrane rupture. We reported a 25-year-oldwoman unbooking patient admitted to the Pusura hospital with a complaint of amniotic fluid leaking fromthe vagina after a traffic accident. The patient is a woman with a history of G2P1A0 at 22-week gestationwith twin pregnancies (monochorionic diamniotic twin pregnancy). There was one live fetus with cephalicpresentation and the other one was papyraceus. Conservative management with a corticosteroid regimento complete the lung maturation was done. At 32-week gestation, the patient was admitted back withspontaneous rupture membranes and the live fetus was seen in lie presentation. She underwent a caesariansection and a premature life female baby was delivered with 1800g of weigh, APGAR score of 7 at 1 minuteand 8 at 5 minutes. The fetus papyraceus was weighed 100g. Both the mother and the baby were dischargedhome in good condition. Fetus papyraceus is a rare condition that describes intrauterine fetal demise in earlypregnancies. It can occur in both single or multiple gestation pregnancies. This case report reported case is apremature rupture of the membranes caused by a traffic accident. A life baby weighing 1800g was deliveredand 100g of weigh of fetus papyraceus in a caesarian section. This case is a diamniotic – monochorionicplacenta. Finally, the healthy baby was discharged 18 days after delivery.